IS THERE ANY AGILITY IN SYSTEMS ENGINEERING?. Issue 4 (28th December 2017) - Díaz Vargas, Diego Armando; Baron, Claude; Esteban, Philippe; Alejandra Gutierrez Estrada, Citlalih Yollohtli
ABSTRACT: Industry employs agile methods more widely, mainly in software development companies. This paper tackles the point of transferring agile methods from software to systems engineering, which raises several questions: Is the transfer immediate, and if not, what are the difficulties? Does the agility refer to the product, the processes, or the project? Do systems engineering standards promote or suggest a kind of agility? Among this panel of questions, a first natural step consists of analyzing if systems engineering standards and guides already include agility in the practices they recommend and what kind of agility. The paper thus focuses on the analysis of one of the most famous current systems engineering standards, the ISO/IEC/IEEE 15288 (2015), with the goal to detect any explicit or implicit reference to agility in this document. Agile methods are beginning to spread in industry; these methods are mainly used in companies whose business is software development. Fields like systems engineering are contemplating these methods to manage the systems engineering technical processes and to lead projects in complex systems development, but some issues must be overcome before implementing such approaches in this domain. Agile methods really emerged with the dissemination of the Agile Manifesto in 2001; however, this document does not give any formal definition of the agile concept, and is clearly focused on software engineering. This paper thus tackles the point of transferring agile methods from software to systems engineering, that includes several questions: Is the transfer immediate? What are the difficulties? Does the agility refer to the product, the processes, or the project? Do systems engineering standards already implicitly consider a kind of agility? Among this panel of questions, a first natural step consists in asking if systems engineering standards and guides would already include any form of agility in the practices they recommend? This paper focuses on the analysis of one of the most famous current systems engineering standards, the ISO/IEC/IEEE 15288 (2015), with the goal to detect any explicit or implicit reference to agility in this document.